Speech defects in head and neck cancer patients - a one year study (1996)
This paper is based on a study of the speech defects in 74 head and neck cancer in-patients seen at the Ear, Nose and Throat Department of the University College Hospital, Ibadan, Nigeria between October 1989 and October 1990. Out of the 74 patients, only 65 had speech problems while 9 were free of speech defects. Hoarseness and rhinolalia clause were found to be the commonest. Other speech detects found were the so called "hot potato" voice and minimal pitch changes